Effect of Conservative Cultivation Technology on the Sustainability of Wheat Productivity And Soil Fertility Properties Compared To Conventional Cultivation System Under The Rain-Fall Conditions In Northeast Syria. - Kaba, Rami; Kert, Yaser; Fatah, Shirin (Jordan Journal of Agricultural Sciences, 2021)
This research was conducted at AL Qamishli Scientific Agricultural Research Center, 1st stability Zone, according to a split-plot design, by planting Durum WHEAT (Cultivar Douma1) in four treatments: 1-Zero-Tillage planting,2-Conventional Tillage, 3-Zero tillage planting with one subsoiling to break the hard layer and Conventional Tillage with subsoiling with three replications for each treatment. The Baldan seeder was used to cultivate the treatment of Zero-Tillage. Whereas the treatment of Conventional Tillage was cultivated using Harrow. The research results for ten years (2008 - 2018) indicated that the conservation agriculture ZT system had a significant effect on increasing wheat productivity compared to Conventional Tillage CT. We found that the average grain yield for the ten years was the highest significantly under the conditions of conservative cultivation 1528 (kg ha-1), with 25% more than conventional cultivation, while the lowest significantly was under the conditions of conventional cultivation 1222 (kg ha-1( Also, one-time subsoiling tillage combined with the conservative cultivation system’s application significantly affected increasing the grain yield 1534 (kg ha-1). Moreover, the average increase for the ten seasons was 25.5% compared to conventional cultivation treatment without deep cultivation. Precipitation use efficiency (PUE) was significantly higher under Conservation Agriculture ZT (14.85 Kg.mm-1. ha-1) followed by ZT+SB (14.77 Kg.mm-1. ha-1) and CT+SB (13.31 Kg.mm-1. ha-1) with increased ratios 20.9% -%20.3 -%8.4 respectively compared with the CT tillage systems (12.28 Kg.mm-1. ha-1). Stability analysis indicated that the Conservation Agriculture ZT system’s yields were less influenced by adverse growing conditions than conventional tillage CT systems, particularly under low rainfall.